Medical approach to disability. A history of a multifaceted relationship - Leone, Cinzia (Medicina Historica, 2020)
Disability expresses an object, but principally also a concept with an outline difficult to define. A concept as much undefined as complex. In comparison to its definition, disability as a concept has not yet been untangled definitely even due to the fact that disability represents by itself the difficulty to trace a stable and certain dividing line. The present paper will offer a discussion of the so-called interpretative models linked to the meaning and the magnitude of disability under a first medical and then sociological point of view. During last decades, in fact, the understanding towards sociological instances in relation with disability have changed remarkably, trying to bridge the gap existing in the past, when disability was observed only as a personal health issue and consequently only under one specific framework of analysis, abstracting it from the boundary conditions and from the society in a de-constructional approach which lead to disregard disability per se. Thus in the times, disability passed from being a personal and medical problem to a phenomenon with its own social impact and a social construction, deviating the observation of disability from the medical and health point of view to a holistic approach, even if with consistent differences in relation to the diverse paradigms of interpretation.